Зависимость эффективности электролюминесцентных индикаторов от параметров источника питания - Lenkov, S. V.; Gunchenko, Yu. A.; Zherevchuk, V. V.; Selukov, А. V. (PE "Politekhperiodika", Book and Journal Publishers, 2008)
The dependencies of the brightness of thin-film electroluminescent indicators on the composition of the active material, as well as on the voltage and frequency of the power supply, have been investigated. An optimal composition of the active material has been selected, and a special power supply has been developed that enables improved efficiency of information perception through automatic adjustment of the brightness of luminescence depending on the illumination level. As a result, the service life and ergonomic characteristics of the information display system are enhanced.